Unique aspects of pain reduction in osteoarthritis of the knee with LMWF-5A - McGrath B (Dove Medical Press, 2015)
Brian McGrath University Orthopaedic Center, Amherst, NY, USA Abstract: Osteoarthritis of the knee (OAK) is a common form of arthritis that can lead to substantial pain and disability. This commentary highlights key aspects of the recently published phase 3 A Efficacy and Safety Study of Two Doses of Intra-Articular Injection of Ampion™ in Adults With Pain Due to Osteoarthritis of the Knee (SPRING) study. SPRING (NCT01839331) was a multicenter, randomized, vehicle-controlled, double-blind trial that evaluated the safety and efficacy of the low-molecular-weight fraction of 5% human serum albumin (LMWF-5A) for treatment of pain, measured by the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) pain scale, in patients with symptomatic OAK (N=329). Patients in this study reflected many characteristics of "real-world" individuals with OAK, with a broad range of disease severity and disability. The most important finding from this study was that treatment with a single intra-articular injection of LMWF-5A led to significant pain reduction in the patients with objective radiographic evidence of severe disease and joint deterioration (Kellgren-Lawrence grade 3; P=0.04 and Kellgren-Lawrence grade 4; P=0.02). The magnitude of pain reduction in the entire cohort treated with LMWF-5A was 42% from baseline and the treatment effect compared with vehicle control (estimated difference in WOMAC pain, -0.25; P=0.004) was also notable, especially relative to a previously reported study of hyaluronic acid, in which only a marginally significant treatment effect was observed (mean difference in WOMAC pain compared with control, -0.15; P=0.047). Significant improvement in physical function observed with LMWF-5A (P=0.04) was also noted and suggests that LMWF-5A may provide therapeutic benefit for those who are limited in the activities of daily living. Intra-articular injection of LMWF-5A was well tolerated, and the adverse event profile was similar to that of control. These results demonstrate significant benefit of LMWF-5A for patients with greatest disability (Kellgren-Lawrence grades 3 and 4) and highest therapeutic need who have limited pharmacologic options for relief of pain associated with OAK. Keywords: human serum albumin, knee, osteoarthritis, pain, Kellgren-Lawrence